Catalytic Oxidation of CO on a Curved Pt(111) Surface: Simultaneous Ignition at All Facets through a Transient CO‐O Complex. Issue 45 (31st August 2020) - Garcia‐Martinez, Fernando; García‐Fernández, Carlos; Simonovis, Juan Pablo; Hunt, Adrian; Walter, Andrew; Waluyo, Iradwikanari; Bertram, Florian; Merte, Lindsay R.; Shipilin, Mikhail; Pfaff, Sebastian; Blomberg, Sara; Zetterberg, Johan; et al.
Abstract: The catalytic oxidation of CO on transition metals, such as Pt, is commonly viewed as a sharp transition from the CO‐inhibited surface to the active metal, covered with O. However, we find that minor amounts of O are present in the CO‐poisoned layer that explain why, surprisingly, CO desorbs at stepped and flat Pt crystal planes at once, regardless of the reaction conditions. Using near‐ambient pressure X‐ray photoemission and a curved Pt(111) crystal we probe the chemical composition at surfaces with variable step density during the CO oxidation reaction. Analysis of C and O core levels across the curved crystal reveals that, right before light‐off, subsurface O builds up within (111) terraces. This is key to trigger the simultaneous ignition of the catalytic reaction at different Pt surfaces: a CO‐Pt‐O complex is formed that equals the CO chemisorption energy at terraces and steps, leading to the abrupt desorption of poisoning CO from all crystal facets at the same temperature. Abstract : The light‐off of the CO oxidation is simultaneous on all Pt crystal surfaces vicinal to the (111) plane, regardless of the reaction conditions, and in contrast with the structural dependence of Pd. Using ambient‐pressure XPS we find that, immediately prior to ignition, atomic oxygen incorporates to the subsurface plane, leading to buckling of the topmost CO‐Pt layer, and effectively equaling the CO desorption temperature at terraces and steps.